PENDAMPINGAN LITERASI FINANSIAL DAN PERENCANAAN INVESTASI DALAM MEMBENTUK POLA PIKIR KEUANGAN REMAJA - Ahmad Qolyubi; Dian Okchatamsi; Agus Munandar (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Low levels of financial literacy among adolescents can hinder their ability to manage money, set priority needs, and choose appropriate investment instruments. Therefore, it is crucial for secondary and vocational school students to acquire financial literacy education from an early age, to prepare themselves for entering the workforce and managing their income independently. This community service program aims to enhance students' financial planning and investment skills through a Participatory Action approach. The activity was implemented at Tiara Aksara Vocational High School in Tangerang on June 15, 2026, involving 49 students. The stages of the activity included needs assessment, planning, workshop implementation, and evaluation through observation and reflection. Topics covered included the importance of emergency funds, investment fundamentals, various investment options, the relationship between risk and return, determining risk profiles, and raising awareness of illegal investments. The results of the activity showed that students gained an improved understanding of personal financial management, establishing emergency funds, selecting investment instruments based on their risk profiles, and the importance of setting financial priorities. This program can serve as an alternative model for financial education applicable to secondary and vocational school students.